2009
DOI: 10.1111/j.1399-0012.2008.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of basiliximab with three different patterns of cyclosporin A initiation in renal transplant from expanded criteria donors and at high risk of delayed graft function

Abstract: This study assays therapy with basiliximab and different patterns of cyclosporin A (CsA) initiation in renal transplant (RT) recipients from expanded criteria donors (ECD) and at high risk of delayed graft function (DGF). A multicentre six-month open-label randomized trial with three parallel groups treated with basiliximab plus steroids, mycophenolate mofetil and different patterns of CsA initiation: early within 24 h post-RT at 3 mg/kg/d (Group 1; n = 38), and at 5 mg/kg/d (Group 2; n = 40), or delayed after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Total CNI avoidance, 3,5,9 -38 CNI minimization, 17,39 -55 and delayed introduction of CNI 49,50,[55][56][57][58][59][60][61][62] were investigated in 32 (n ϭ 5791), 17 (n ϭ 4131), and 10 studies (n ϭ 1519) respectively. Two studies 50,55 investigated CNI delay followed by minimization: to avoid "double counting" these were analyzed as "delay" studies initially, but if subgroup analyses were necessary (due to heterogeneity), then the same study was considered separately in both the "minimization" and "delay" subanalyses.…”
Section: Resultsmentioning
confidence: 99%
“…Total CNI avoidance, 3,5,9 -38 CNI minimization, 17,39 -55 and delayed introduction of CNI 49,50,[55][56][57][58][59][60][61][62] were investigated in 32 (n ϭ 5791), 17 (n ϭ 4131), and 10 studies (n ϭ 1519) respectively. Two studies 50,55 investigated CNI delay followed by minimization: to avoid "double counting" these were analyzed as "delay" studies initially, but if subgroup analyses were necessary (due to heterogeneity), then the same study was considered separately in both the "minimization" and "delay" subanalyses.…”
Section: Resultsmentioning
confidence: 99%
“…[43] The GFR (primary endpoint) was not significantly different between the immediate minimal-dose, immediate reduceddose, and the delayed-dose groups at 3 (46.1, 47.9, and 44.7 mL min) or 6 (43.1, 48.0, and 47.2 mL min) months. [43] The GFR (primary endpoint) was not significantly different between the immediate minimal-dose, immediate reduceddose, and the delayed-dose groups at 3 (46.1, 47.9, and 44.7 mL min) or 6 (43.1, 48.0, and 47.2 mL min) months.…”
Section: Calcineurin Inhibitor-sparing Regimensmentioning
confidence: 84%
“…[43] The GFR (primary endpoint) was not significantly different between the immediate minimal-dose, immediate reduceddose, and the delayed-dose groups at 3 (46.1, 47.9, and 44.7 mL min) or 6 (43.1, 48.0, and 47.2 mL min) months. [43] Graft and patient survival at 6 months was also similar between treatment groups. [43] Graft and patient survival at 6 months was also similar between treatment groups.…”
Section: Calcineurin Inhibitor-sparing Regimensmentioning
confidence: 84%
See 1 more Smart Citation
“…The extension of this study with a mean follow up of 30 months demonstrated comparable creatinine clearance between groups. NI2A Study Group in Spain also compared different patterns of CsA initiation in renal transplant recipient from expanded criteria donors and high risk of DGF: early low-dose CsA (3 mg/kg/day, n =38), early standard-dose CsA (5 mg/kg/day, n =40), and delayed standard-dose CsA (5 mg/kg/day 7–10 days after transplant, n =36) 63. This multicenter six-month, open-label, randomized trial with basiliximab, MMF, and steroids revealed no differences among groups in six months GFR, DGF rate (31%, 38%, and 42% for early low-dose CsA, early standard-dose CsA, delayed standard-dose CsA, respectively), and BPAR rate (5%, 13%, and 11%), although combined clinically treated and BPAR rate was significantly higher in the delayed CsA group (5%, 15%, and 25%).…”
Section: Il-2ra In Cni-sparing Protocolsmentioning
confidence: 99%